2011
DOI: 10.1080/00222348.2010.540987
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Copper and Polytetrafluoroethylene (PTFE) on Thermal Conductivity and Tribological Behavior of Polyoxymethylene (POM) Composites

Abstract: The effects of copper and polytetrafluoroethylene (PTFE) on thermal conductivity and tribological behavior of polyoxymethylene (POM) composites were investigated by a hot disk thermal analyzer and an M-2000 friction and abrasion testing machine. The results indicated that the incorporation of 3 wt% copper particles into POM had little effect on the thermal conductivity of POM composites, but led to the decreased friction coefficient and wear rate of composites. As the copper content was increased, the thermal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 25 publications
(27 reference statements)
0
19
0
Order By: Relevance
“…This is because POM has high mechanical strength and unique properties such as excellent abrasion resistance, low friction coefficient, fatigue resistance, noiseless performance, lightweight, oil-less conditions, mouldability, higher melting point and low cost [1][2][3][4][5][6][7][8][9][10]. As such POM is considered as a major class of tribopolymers widely used in wear applications.…”
Section: Introductionmentioning
confidence: 99%
“…This is because POM has high mechanical strength and unique properties such as excellent abrasion resistance, low friction coefficient, fatigue resistance, noiseless performance, lightweight, oil-less conditions, mouldability, higher melting point and low cost [1][2][3][4][5][6][7][8][9][10]. As such POM is considered as a major class of tribopolymers widely used in wear applications.…”
Section: Introductionmentioning
confidence: 99%
“…Th e debris morphology indicated the adhesive wear and abrasive wear mechanisms of POM/Cu composites. Further, it was reported that incorporation of PTFE into POM-Cu composites had a negligible eff ect on the thermal conductivity of composites, but helped in the formation of a continuous and uniform transfer fi lm, and resulted in the reduction in the friction coeffi cient and wear rate of composites [90]. Th e POM/15% Cu/10% PTFE composite, with a value of wear rate similar to unfi lled POM possessed higher thermal conductivity and lower friction coeffi cient (Fig.…”
Section: Tribological Properties and Wear Resistance Of Pom-based Nanmentioning
confidence: 99%
“…21 Eff ect of Cu content on (a) the friction coeffi cient and (b) wear rate of POM composites with and without PTFE[90].…”
mentioning
confidence: 99%
“…Recently, more and more researchers have put an emphasis on the synergistic effects of various fillers in improving the friction and wear properties of polymers [17][18][19]. However, the main focus of examinations of the tribology performance of POM-based composites was concentrated on the selection and collocation of additives [17], surface treatment of fillers [16], processing parameters [20] and sliding conditions [21,22].…”
Section: Introductionmentioning
confidence: 99%